Plot dan Pemlotan Pada Novel 'Kereta Semar Lembu' Karya Zaky Yamani - Nurul Aini (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This study examines the plot and narrative structuring in Zaky Yamani’s novel “Kereta Semar Lembu”, a contemporary literary work offering a complex and innovative narrative. The background of this research focuses on the importance of understanding how plot structure and narrative techniques can affect readers' experiences and emotional engagement. The aim of the study is to analyse the main plot elements of the novel and to explore the narrative techniques used to build tension and climax. The research methods employed include structural and narrative analysis. Structural analysis identifies and outlines plot components such as exposition, conflict, climax, and resolution, while narrative analysis explores narrative techniques such as mixed and episodic plotting. The primary data source is the novel *Kereta Semar Lembu*, with data collection procedures involving in-depth reading and recording of narrative techniques. The main findings indicate that Yamani effectively uses mixed and episodic plotting techniques to create a dynamic and tension-filled narrative. Flashbacks and episodic structure enrich the story, providing emotional depth and building tension towards a satisfying climax. The study concludes that the narrative techniques used in the novel not only enhance the narrative structure but also improve the overall reading experience. The research suggests conducting comparative studies with other works to gain deeper insights into the evolution of narrative techniques in contemporary Indonesian literature.